BIFURCATION DIAGRAM FOR TWO DIMENSIONAL LOGISTIC MAPPING - M. I. Islamova; R. R. Kutlumuratov; A. J. Ismailov (Journals Park Publishing, 2025)
The present paper is devoted to investigation of the multidimensional case of the logistic mapping on the plane to itself. In this paper we learnt the properties of Julia and Mandelbrot sets for some two-dimensional logistic mappings. Julia and Mandelbrot sets help to define asymptotical behavior of the trajectories of certain mappings. The analytical solutions of the equations for finding fixed and periodic points and the computational simulations for describing Julia and Mandelbrot sets are the main results of this paper.
Keywords: Logistic mapping, bifurcation diagram, multidimensional case.